SOME ASPECTS OF EPIDEMIOLOGY AND ETIOPATHOGENESIS OF METABOLIC SYNDROME - S. M. ABDULLOZODA (Avicenna Tajik State Medical University, 2020)
A review of literature data carried out on the most important aspects of epidemiology, risk factors and pathogenesis of metabolic syndrome (MS). Metabolic syndrome has been found in approximately one quarter of the world's population, and, despite the large-scale treatment, preventive and health-improving promotion programs on a global scale, the number of persons with MS tends to increase annually, especially among young ablebodied age. There are many risk factors in its genesis, including genetic predisposition, low physical activity, poor diet, smoking, intestinal microbiota, obstructive sleep apnea syndrome and others, the role of most of which needs to be studied in more depth. Many criteria have been proposed for the diagnosis of MS, each of them has its own advantages and disadvantages. With MS, most organs and systems are affected, and with the combined involvement of the cardiovascular, endocrine, urinary, digestive and respiratory systems burdened clinical course of MS. In connection with the above, there is a reason for further scientific research to identify the causes and risk factors for the development of MS, development of preventive ways of prevention, preventive diagnostics and early treatment of MS.